Innovations in reagent manufacturing to support the global diagnostics supply chain - Anna R. Bird; Jacqueline C. Linnes; Laud Anthony Basing; Elizabeth A. H. Hall (Frontiers in Public Health, 2026)
Diagnostics are not only tools for clinical decision making, but also drivers of the healthcare supply chain. They quantify and monitor the prevalence of disease across global populations. At high levels, this population health data is used to inform the purchasing and distribution of health care goods. There is overwhelming evidence that access to diagnostics is limited in low-and middle-income countries. This is true for both in-vitro molecular diagnostics and diagnostic imaging, but the scope of this work is limited to the former. While the factors contributing to limited access are numerous, interconnected, and complex, we propose a method to alleviate some restraints within the supply chain: distributed and local manufacturing of key biological reagents, or active diagnostics ingredients (ADIs). In addition to shifting the geographical boundaries of manufacturing and moving goods closer to areas of deployment, this could reduce global power imbalances by redistributing ownership of diagnostics goods, reagents, and intellectual property.